Analiza translatywna niemieckich, polskich i hiszpańskich compositów - Machowski, Szymon (Investigationes Linguisticae, 2010)
The aim of this article is to present ways of translating both subordinative and coordinative German compounds into Polish and Spanish. The translation analyses of compounds is based on three parallel sets of compounds selected from the German, Polish and Spanish versions of The Trial by Franz Kafka. In the first part of the article, the compounds from the sets are classified in view of semantic relations between constituents of the compounds. Then the ways of translating German compounds representing each compound type into Polish and Spanish are discussed.